Amphiphilic Polymer‐Based Fluorescent Probe for Enantioselective Recognition of Amino Acids in Immiscible Water and Organic Phases. Issue 71 (22nd November 2017) - Nian, Shifeng; Pu, Lin
Abstract: Atom transfer radical polymerization (ATRP) of N ‐isopropylacrylamide was conducted in the presence of a 3, 3′‐diformyl‐1, 1′‐BINOL‐based diinitiator (BINOL=1, 1′‐bi‐2‐naphthol) to give polymer ( S )‐7, which was soluble in both water and common organic solvents. Polymer ( S )‐7 in combination with Zn 2+ in aqueous solution (BICINE buffer at pH 8.80) showed highly enantioselective fluorescence enhancement in the presence of a number of amino acids. It was found that chloroform can be used to extract the aqueous polymer–Zn 2+ –amino acid solution and the resulting chloroform extract maintained the highly enantioselective fluorescence response. Thus, the enantiomeric composition of a chiral amino acid can be determined in the two immiscible solvents of water and chloroform. The aqueous polymer–Zn 2+ –amino acid solution showed a lower critical solution temperature (LCST) at 34 °C, above which the polymer–Zn 2+ –amino acid adduct precipitated out. Measuring the fluorescence of the precipitate redissolved in the aqueous buffer solution showed the retention of the high enantioselectivity. Both the chloroform extraction and the thermo‐induced precipitation have allowed the fluorescence response of the sensor toward amino acids to be measured away from the original substrate solution. These two strategies should minimize the interference by other reaction components on the fluorescence measurement when the sensor is applied to analyze the asymmetric reaction screening experiments. Abstract : Enantioselective fluorescent recognition of amino acids can be conducted in two immiscible phases: water and chloroform. Thermo‐precipitation provides another strategy to measure the substrate‐sensor response away from the orginal substrate solution.